2013
DOI: 10.1002/grl.50844
|View full text |Cite
|
Sign up to set email alerts
|

Direct temperature and salinity acoustic full waveform inversion

Abstract: [1] Recent work has shown that Full Waveform Inversion could be suitable to extract physical properties such as sound speed (c), density ( ), temperature (T), and salinity (S) from the weak impedance contrasts associated with the ocean's thermohaline fine structure.The seismic inversion approaches proposed so far are based on the iterative inversion of c from multichannel seismic data, while the rest of parameters (T, S, and ) are determined in a second step using two equations of state and a local T-S empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Because of that, we consider that the synthetic FWI inversion presented by Bornstein et al . [] is very promising since they do not use any T‐S relation and invert independently temperature and salinity directly from the acoustic wave minimizing the error in potential density. As a final test, we have applied the method of Bornstein et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of that, we consider that the synthetic FWI inversion presented by Bornstein et al . [] is very promising since they do not use any T‐S relation and invert independently temperature and salinity directly from the acoustic wave minimizing the error in potential density. As a final test, we have applied the method of Bornstein et al .…”
Section: Discussionmentioning
confidence: 99%
“…As a final test, we have applied the method of Bornstein et al . [] to invert potential density from the synthetic reflectivity along a section of a meddy. The result, which is shown in Figure , corroborates that potential density varies along the continuous reflector of the top of the core and hence reflectivity is not isopycnal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MCS systems are widely used in solid earth exploration and research, and they started to be used in oceanography following the preliminary results of Gonella and Michon [1988] and the seminal work of Holbrook et al [2003], which opened a new branch in operational oceanography that has been called "seismic oceanography." Subsequently, a series of studies have demonstrated the potential of conventional MCS data to image the thermohaline fine structure of the oceans [Biescas et al, 2008;Buffett et al, 2009;Sheen et al, 2012;Ménesguen et al, 2012], to extract water properties such as sound speed, temperature, or salinity [Papenberg et al, 2010;Bornstein et al, 2013;Biescas et al, 2014;Padhi et al, 2015] or to provide information on internal wave dynamics and turbulence [Holbrook and Fer, 2005;Sheen et al, 2009;Krahmann et al, 2008;Falder et al, 2016], all with extraordinary detail in the horizontal dimension.…”
Section: Study Area and Data Acquisition Systemmentioning
confidence: 99%